Scaffold proteins ITSN1 and ITSN2 interact with nuclear RNA-binding proteins - Pankivskyi, S.V.; Senchenko, N.V.; Busko, P.B.; Rynditch, A.V. (Вiopolymers and Cell, 2019)
Aim. To identify novel ITSN1 and ITSN2 partners among RNA-binding proteins (RBPs) involved in regulation of mRNA processing. Methods. GST pull-down, immunoprecipitation assays and bioinformatics analysis was used to identify other RBPs that could interact with ITSN1 and ITSN2 proteins. Results. ITSN1 and ITSN2 SH3 domains interacted in vitro with nuclear RBPs SAM68, WBP11, and LARP6. ITSN1 and ITSN2 also co-precipitated with SAM68 and LARP6 from 293 cell lysates. Finally, the bioinformatics analysis identified more than 500 nuclear RBPs that contained several SH3 domain-interacting proline motifs and could bind ITSN1/2. Conclusions. ITSN1 and ITSN2 SH3 domains bind nuclear RBPs SAM68, LARP6, and WBP11 in vitro, form complexes with SAM68 and LARP6 in 293 cells, and potentially could interact with other nuclear RBPs containing SH3 domain-interacting motifs.